2017
DOI: 10.1016/j.ehb.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of urbanization to non-communicable diseases: Evidence from 173 countries from 1980 to 2008

Abstract: It is widely believed that the expanding burden of non-communicable diseases (NCDs) is in no small part the result of major macro-level determinants. We use a large amount of new data, to explore in particular the role played by urbanization - the process of the population shifting from rural to urban areas within countries - in affecting four important drivers of NCDs world-wide: diabetes prevalence, as well as average body mass index (BMI), total cholesterol level and systolic blood pressure. Urbanization is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 50 publications
6
63
0
Order By: Relevance
“…Over 50 million people, almost 18% of the U.S. population, live in low-income areas without convenient access to a supermarket (Rhone et al, 2017). In high-income, highly urbanized countries, diabetes correlates positively with the percentage living in urban areas (Goryakin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 50 million people, almost 18% of the U.S. population, live in low-income areas without convenient access to a supermarket (Rhone et al, 2017). In high-income, highly urbanized countries, diabetes correlates positively with the percentage living in urban areas (Goryakin et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…From a gene-culture evolutionary perspective, the recent rise in obesity rates, occurring across the Developed world (Goryakin et al, 2017), is unprecedented. In the past, human niche construction evolved over a time scale of centuries or millennia (Creanza and Feldman, 2016;Milot et al, 2011).…”
mentioning
confidence: 99%
“…Urbanization is the process of human migration from rural to urban areas (Goryakin et al 2017) and involves change of land use from agricultural to non-agricultural (Li et al 2017). Generally, urbanization is considered as the foundation for advancing human civilization (Christensen and McCord 2016) and has had a significant impact on society.…”
Section: Introductionmentioning
confidence: 99%
“…During, the last decades, NCDs rate increases all over the world and becomes a public health threat. Many studies were interested in NCDs and reported that in general, these diseases are chronic, which cause disabilities for human, decrease his performance and are the principal cause of death (Goryakin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Second, the majority of them appear in the fourth decade of human life. Third, NCDs are supposed to start early, progressively and silently during human lifespan (Goryakin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%